Inovasi Industri 5.0 dalam Mentransformasi Warisan Kuliner Tradisional: Analisis Implementasi pada Bisnis Kuliner di Medan - Surya Sevi Wijayanna (Jurnal Manajemen Riset Inovasi, 2024)
The traditional food and beverage industry in Medan, Indonesia, is undergoing significant changes as Industry 5.0 technology becomes more integrated. This research explores the impact of this transformation through data analysis from 143 traditional culinary businesses. The focus is on evaluating the extent to which Industry 5.0 has been adopted, identifying factors that drive or hinder its adoption, and analyzing how this affects business operations and customer experiences. We utilized Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine the relationship between business characteristics, workforce readiness, Industry 5.0 adoption, and its implications for operational and customer experiences. We used descriptive statistics to understand demographic and technological profiles, while measurement model evaluation demonstrated the validity and reliability of our survey. Path analysis and bootstrap analysis were employed to confirm relationships, while fit model evaluation, R², and Q² provided insights into overall model robustness. Our findings contribute to academic knowledge, provide guidance for business owners in making strategic decisions, and establish standards for future research on Industry 5.0 adoption in the traditional sector.